Determinants of Staff Performance at the Kerinci Regency Education Office: The Role of the Self-Assessment System, Training Methods, and Training Materials - Jeke Julpitra; Rio Baviga (International Journal of Business and Quality Research, 2026)
Employee performance plays an important role in supporting the effectiveness of public organizations, particularly in delivering quality educational services. This study aims to analyze the effect of the Self-Assessment System, Training Methods, and Training Materials on employee performance at the Kerinci Regency Education Office, both partially and simultaneously. This study employed a quantitative approach involving 60 employees selected through saturated sampling. Data were collected using questionnaires and analyzed through multiple linear regression, t-tests, and F-tests. The results show that the Self-Assessment System has a positive and significant effect on employee performance, contributing 15.62%. Training Methods also have a positive and significant effect, contributing 6.88%, while Training Materials have a significant effect with a contribution of 3.88%. Simultaneously, the Self-Assessment System, Training Methods, and Training Materials significantly affect employee performance, with a combined contribution of 31.3%, while the remaining 68.7% is influenced by other factors outside the research model. These findings emphasize the importance of strengthening self-assessment practices and improving training methods and materials to enhance employee performance at the Kerinci Regency Education Office.